AUTONOMY OF THE WILL IN COUPLE´S AFFECTIVE RELATIONSHIPS (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
If there is a branch within Private Law in general and Civil Law in particular where their institutions has been foremost considered to be of Public Order, it has been Family Law, or - if preferred and in recognition of the diverse family forms - of "Families’ Law".True reflection of this, in the nineteenth-century codes -of which Vélez Sarsfield's Civil Code was not an exception- and even after its successive reforms, rules of Family Law were beyond the scope of the autonomy of the will, and therefore, of the possibility of the parties to self-regulate their relationships.Nevertheless, society has been mutating, demanding recognition of "other ways of living as a family", forging a change of paradigm that results in a tendency towards "privacy and / or autonomy", and therefore, a step backwards from Public Order, where family issues are eventually more private than public.From this starting point, this time we are interested in analyzing the relationship between these principles in a couple’s affective relationship, on the understanding that in both is reflected, with an increasing prevalence, the autonomy of the will.
Keywords: Autonomy of the will; public order; family; couple